JAPAN KARATE ASSOCIATION ( JKA ) SEBAGAI AKTOR TRANSNASIONAL DALAM MENDUKUNG DIPLOMASI BUDAYA JEPANG MELALUI OLAHRAGA DI INDONESIA - , RIZA VUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cultural diplomacy is one part of the Japan's foreign policy which is very important in the aftermath of the war. The diplomacy run by the country aims for getting a good image in global fellowship